2008
DOI: 10.1074/jbc.m708318200
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the Calcium Sensing Receptor Inhibits E-cadherin-mediated Cell-Cell Adhesion and Calcium-induced Differentiation in Human Epidermal Keratinocytes

Abstract: and impairing differentiation in keratinocytes (8). One of the immediate cellular responses to Ca 2ϩo in epithelial cells is the formation of cell-cell contacts, a process mediated by the adhesion molecule E-cadherin (10). E-cadherin is a major classical cadherin in keratinocytes and is expressed throughout the epidermis (11). Upon Ca 2ϩ o stimulation, the extracellular portion of E-cadherin interacts with E-cadherin molecules on the surface of neighboring cells, whereas its cytoplasmic tail interacts with ␤-(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(116 citation statements)
references
References 42 publications
4
111
1
Order By: Relevance
“…This scenario predicted that adherens junction components or a different factor, perhaps the calcium receptor, CaR, responded to extracellular calcium by initiating intracellular calcium release (Tu et al, 2011;Xie & Bikle, 2007;Tu et al, 2007;Tu et al, 2008). Confi rming the involvement of intracellular calcium, Darier disease patients carrying a mutant form of the intracellular calcium pump, SERCA2, suffer from severe skin erosions attributed to desmosome loss (Sakuntabhai et al, 1999).…”
Section: Assembly: Requirements For Initiating Desmosome Assemblymentioning
confidence: 99%
“…This scenario predicted that adherens junction components or a different factor, perhaps the calcium receptor, CaR, responded to extracellular calcium by initiating intracellular calcium release (Tu et al, 2011;Xie & Bikle, 2007;Tu et al, 2007;Tu et al, 2008). Confi rming the involvement of intracellular calcium, Darier disease patients carrying a mutant form of the intracellular calcium pump, SERCA2, suffer from severe skin erosions attributed to desmosome loss (Sakuntabhai et al, 1999).…”
Section: Assembly: Requirements For Initiating Desmosome Assemblymentioning
confidence: 99%
“…The CaSR coordinates these activities through regulation of a myriad of signaling pathways, including EGFR signaling, MAPK cascades and Ecadherin signaling [3,36,37,47,[50][51][52][62][63][64]. However, few studies have assessed the cell-or tissue-specificity of the cascades activated by engagement of the CaSR or determined the particular roles of the signaling cascades, leaving considerable room for discovery in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, CaSR signaling also has been implicated in regulating colonic epithelial cell differentiation and keratinocyte differentiation through the activation of E-cadherin signaling in a Rhodependent manner with filamin A involvement (Fig. 2) [62][63][64]. Chakrabarty and colleagues demonstrated that stimulation of the CaSR through extracellular calcium increased the expression of the tumor suppressor on colon carcinoma cells, and concomitantly reduced the activation of -catenin/T-cell factor, leading to the suppression of their malignant behavior [63].…”
Section: Intracellular Signalingmentioning
confidence: 99%
“…The colocalisation of adherens junction proteins to secretory granules (Hodgkin et al 2007) suggests that the adherens junction may play a novel role in b-cell function, both in terms of b-cell proliferation (Carvell et al 2007) and insulin secretion (Hodgkin et al 2007, Rogers et al 2007. Neutralising ECAD-mediated cell adhesion decreases glucose-evoked synchronicity in Ca 2C signals between adjacent cells within islets (Rogers et al 2007) and evidence from human epidermal keratinocytes suggests that inactivation of the CaR suppresses the assembly of the ECAD-cateninphosphotidylinositol 3-kinase (PI3K) complex (Tu et al 2008). These data provide compelling evidence that the CaR influences multiple functions that ultimately regulate synchronicity of Ca 2C activity between b-cells within the islet and thus dramatically impinge on insulin secretion.…”
Section: Car: a Role In Cell Adhesion And Proliferation In The Isletmentioning
confidence: 99%